2018
DOI: 10.1016/j.ijpddr.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

High level efficacy of lufenuron against sea lice (Lepeophtheirus salmonis) linked to rapid impact on moulting processes

Abstract: Drug resistance in the salmon louse Lepeophtheirus salmonis is a global issue for Atlantic salmon aquaculture. Multiple resistance has been described across most available compound classes with the exception of the benzoylureas. To target this gap in effective management of L. salmonis and other species of sea lice (e.g. Caligus spp.), Elanco Animal Health is developing an in-feed treatment containing lufenuron (a benzoylurea) to be administered prior to seawater transfer of salmon smolts and to provide long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 75 publications
(122 reference statements)
1
14
0
Order By: Relevance
“…No significant difference was found in the transcriptional levels in LF-treated nauplius II, while for DFB, HX, and TFB only slightly up- or down-regulation were found in one investigated gene. These results are in accordance with other studies where the transcriptional level of chitin metabolism genes was not affected by CSI treatment [17,54]. In this study, LsCHS1 was the only gene that showed a different transcriptional level in more than one CSIs tested.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No significant difference was found in the transcriptional levels in LF-treated nauplius II, while for DFB, HX, and TFB only slightly up- or down-regulation were found in one investigated gene. These results are in accordance with other studies where the transcriptional level of chitin metabolism genes was not affected by CSI treatment [17,54]. In this study, LsCHS1 was the only gene that showed a different transcriptional level in more than one CSIs tested.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study in L . salmonis showed that lufenuron-treated nauplius had a less electron-dense layer, poorly organized epicuticle, and a diffuse procuticle [17], which could be a result of less chitin production and could explain the flexible cuticle structure of the affected copepodids observed in the present study.…”
Section: Discussionmentioning
confidence: 91%
“…We infested the fish by exposing them to copepodid (i.e., larval) L. salmonis as described in Poley et al 81 and Whyte et al 82 . Briefly, adult female lice with egg strings were collected from sea-cage sites in Bay of Fundy, New Brunswick (NB), in August 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Freshwater treatments contributed 5.7 and 5.0% of the total registered NMM treatments in 2017 and 2018, respectively (Hjeltnes et al 2019). In addition to freshwater and warm water treatments and prophylactic skirts, other methods in development include novel chemotherapeutants (Poley et al 2018) and selective breeding for sea louse resistant Atlantic salmon (Gharbi et al 2015).…”
Section: Sea Louse Biology and Farming Techniquesmentioning
confidence: 99%